Library Management Advocacy Study of IAIN Fattahul Muluk Papua Library Program in Realizing Digital Library in 2023 - Sileuw, Marwan; Tuwaji, Tuwaji; Rengiwur, Gazali Husin (Pelopor Publikasi Akademika, 2023)
The study of the IAIN Fattahul Muluk Papua Library program in realizing a digital library is a form of adjustment to technological developments in improving its competence as a supporter of the implementation of the Tri Dharma of Higher Education according to the digital era. The discussion of this study uses the theory of Challenge and Response proposed by Arnold Y. Toynbee. The challenges and responses in the program have reinforced the theory. Some responses are shown by the existence of programs in various components, namely the digital collection component of e-books has held 421 titles, 1,151 copies, developing an institutional Repository as a forum for campus community papers in digital form, and other supporting facilities, such as Turnitin Plagiarism Checker Online. The components of library services, both user services and technical services, also lead to the digitization system. For lending and returning printed books, e-books, free library certificates according to computerized and digitized data. Technical services through the migration program of processing library materials, especially printed books consisting of 5,668 titles, 15,589 copies have been and are being reprocessed to comply with national library standards. Library implementation and management component programs that emphasize reporting systems are a hallmark of good library governance. The Cooperation Program followed up by comparative studies with UIN Mataram and with the National Library of the Republic of Indonesia is a step forward. The existence of additional programs from librarianship organizations implemented such as the Indonesian Higher Education Library Forum (FPPTI), the Indonesian Librarian Association (IPI) of Papua Province shows the level of public trust in the ability of librarians in particular and the IAIN Fattahul Muluk Papua Library in general